NOR1 Suppresses Cancer Stem‐Like Cells Properties of Tumor Cells via the Inhibition of the AKT‐GSK‐3β‐Wnt/β‐catenin‐ALDH1A1 Signal Circuit. Issue 10 (27th March 2017) - Wang, Wei; Yi, Mei; Chen, Shengnan; Li, Junjun; Zhang, Haijing; Xiong, Wei; Li, Guiyuan; Li, Xiaoling; Xiang, Bo
Abstract : Cancer stem cells (CSCs) play a key role in tumor radiotherapy and chemotherapy resistance, relapse, and metastasis, and are primarily maintained in a resting state in vivo. The failure of conventional therapies to target CSCs is the main cause of treatment failure. The discovery of CSCs in nasopharyngeal carcinoma (NPC) tumors is becoming more prevalent; however, the understanding of the mechanisms underlying the maintenance of tumor stemness is still limited. We previously cloned NOR1, a tumor suppressor gene downregulated in NPC cell lines and tissues. In this study, we demonstrate that Wnt/β‐catenin and ALDH1A1 form a signal circuit and that NOR1 antagonizes the tumor stem cell‐like phenotype in NPC cell lines: the ectopic overexpression of NOR1 reduced β‐catenin and ALDH1A1 expression; β‐catenin/TCF4 targeted the regulation of ALDH1A1 transcription in NPC cells; silencing ALDH1A1 reduced AKT (total and phosphorylated) and GSK‐3β (phosphorylated) expression; and eventually feedback decreased β‐catenin expression levels. We also found that NOR1 expression decreased cancer stem‐like cell properties of NPC cells, reduced their ability to form tumor spheroids in vitro, reduced tumorigenicity in nude mice in vivo, and increased sensitivity to chemotherapy agents. Taken together, our findings illustrated a new function of NOR1 that suppresses cancer stem‐like cell properties in tumor cells by inhibiting the AKT‐GSK‐3β‐Wnt/β‐catenin‐ALDH1A1 signal circuit. The study suggests that NOR1 deletion expression in NPC cells may be a potential molecular target for cancer stem cell therapy. J. Cell. Physiol. 232: 2829–2840, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Cancer stem cells (CSCs) play a key role in tumor radiotherapy and chemotherapy resistance, relapse, and metastasis. Our findings illustrated a new function of NOR1 that suppresses cancer stem‐like cell properties in tumor cells by inhibiting the AKT‐GSK‐3β‐Wnt/β‐catenin‐ALDH1A1 signal circuit.